(untitled) (Asian Journal of Plant Biology, 2013)
Heavy metals are toxic elements that are beneficial in industrial process but are toxic to organisms at certain levels once they enter the environment. Hence their monitoring are urgently important. Instrumental analyses are the current accepted method but are cumbersome, time-consuming, expensive and required highly-skilled technical personnel to operate them. Assays using microorganism and their products such as enzymes are beginning to emerge as plausible methods for preliminary screening followed by instrumental methods. This approach cut costs and time but the challenge is to find a robust enzyme system that could withstand variation in environmental conditions and sampling. Various enzymes such as urease, acetylcholinesterase, invertase and glucose oxidase have been used but their activity is strongly affected by extreme variation of pHs and temperature often associated with real samples. The plant proteases such as papain and bromelain have been proven to be robust enzymes for the detection of heavy metals and are the subject of this mini review.